Keperluan Garis Panduan Dan Etika Islam Dalam Penyelidikan Kecerdasan Buatan - Aliff Nawi; Mohd Faiz Mohd Yaakob; Zalmizy Hussin; Nadia Diyana Mohd Muhaiyuddin; Mohd Al Adib Samuri; Ab. Halim Tamuri (USIM Press, 2024)
Vol. 26 No. 2 (2021): Special Edition